PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR MATERI PERPINDAHAN PANAS IPA KELAS IV - Lestari, Emil; Arrasyid, Harun; Wijaksono, Agus (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
The background to the problem of this research is that science learning in class IV SDN 2 Kebaman Srono is still less effective and is delivered conventionally by the teacher. As a result, students do not want to listen to the teacher's explanation and their interest and learning outcomes also decrease. As a result, research must be conducted to improve the quality of learning by using approaches that can increase student interest. This Classroom Action Research (PTK) aims to explain the use of experimental methods in science learning and increase the interest and learning outcomes of class IV students after the method is applied. SDN 2 Kebaman Srono is the subject of this qualitative research. The sequence of research activities includes (1) planning, (2) implementation, (3) observation, and (4) reflection. The research results are as follows: (1) the application of the experimental method in science learning was carried out in two cycles; (2) the application of experimental methods in science learning can increase student interest and learning outcomes, as shown by the increase in learning completeness in Cycle I (60%) and Cycle II (85%).